A Bioethos for Bodies: Respecting a Priceless Resource. Issue 4 (25th February 2019) - Champney, Thomas H.
Abstract : The value that willed body donors provide to medical education is priceless. Their precious gift helps to teach anatomy, spatial relationships between morphological structures, anatomical variation, and professionalism to medical students in a way that plastic models, podcasts, and lectures cannot. They are also an important resource for medical research and a wide variety of postgraduate training opportunities. While many body donation programs throughout the world are nonprofit organizations, there are body donation companies in the United States that sell donors for‐profit. These "body brokers" have accumulated large profits from this business. It is incongruous that others would profit from such a priceless, freely donated gift. To prevent this incongruity, it is proposed that the international anatomical community develop a normative culture (a bioethos) for body donation programs. This would involve the conscious and systematic development of ethical principles for the day‐to‐day policies and practices of institutions that collect and use human bodies. With the development of this bioethos, a cultural shift in how donors are treated would occur and, over time, this would become the normal practice. These principles would become fundamental and foundational for the procurement and use of priceless human tissues.